2021
DOI: 10.3389/fphy.2021.719534
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Cation Stoichiometry on the Crystalline Structure and Superconductivity in Nickelates

Abstract: The recent discovery of superconductivity in infinite-layer nickelate films has aroused great interest since it provides a new platform to explore the mechanism of high-temperature superconductivity. However, superconductivity only appears in the thin film form and synthesizing superconducting nickelate films is extremely challenging, limiting the in-depth studies on this compound. Here, we explore the critical parameters in the growth of high-quality nickelate films using molecular beam epitaxy. We found that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 53 publications
0
27
0
Order By: Relevance
“…For IL nickelates, a close relation and possible analogy to cuprate superconductors was suggested already in 1999 [11], and since the first discovery of superconductivity in the IL nickelate (Nd,Sr)NiO 2 [12], the observation of superconductivity has been confirmed [13][14][15] and extended to (Pr,Sr)NiO 2 [16], (La,Sr)NiO 2 [17], (La,Ca)NiO 2 [18], and Nd 6 Ni 5 O 12 [19]. Furthermore, a recent work reported superconductivity not only for films grown on SrTiO 3 substrates but also on LSAT [20], which provides enough evidence to consider thin-film nickelates as a novel class of superconductors.…”
Section: Introductionmentioning
confidence: 90%
“…For IL nickelates, a close relation and possible analogy to cuprate superconductors was suggested already in 1999 [11], and since the first discovery of superconductivity in the IL nickelate (Nd,Sr)NiO 2 [12], the observation of superconductivity has been confirmed [13][14][15] and extended to (Pr,Sr)NiO 2 [16], (La,Sr)NiO 2 [17], (La,Ca)NiO 2 [18], and Nd 6 Ni 5 O 12 [19]. Furthermore, a recent work reported superconductivity not only for films grown on SrTiO 3 substrates but also on LSAT [20], which provides enough evidence to consider thin-film nickelates as a novel class of superconductors.…”
Section: Introductionmentioning
confidence: 90%
“…Two of them may be just stoichiometry and sample quality. The R:Ni flux ratio used during the growth of the perovskite films, for example, has been reported to be an important factor for their subsequent reduction into the infinite-layer phase and hence for the observation superconductivity [40]. Beyond that, samples synthesized in nominally similar conditions can easily show substantial variations in the superconducting T c and even stay nonsuperconducting [5].…”
Section: Epitaxial Strainmentioning
confidence: 99%
“…The discovery of nickel superconductors [1] has attracted renewed attention to superconductivity in strongly correlated electron systems [2][3][4][5][6][7]. So far, superconductivity has been found in film samples of doped infinite-layer nickelates RNiO 2 (R = Nd, Pr, and La) [1,[8][9][10][11][12][13][14][15][16] and a quintuple-layer nickelate Nd 6 Ni 5 O 12 [17]. Although the nature of the superconductivity is largely unknown, the pairing mechanism is likely to be unconventional: Theoretically, a phonon calculation for NdNiO 2 has shown that the electron-phonon coupling is too weak to explain the superconductivity with a transition temperature on the order of 10 K [18].…”
Section: Introductionmentioning
confidence: 99%